The Impact of Male Migration from Morocco to Europe on Women: A Gender Approach - Sadiqi, Fatima; Ennaji, Moha (Finisterra, 2004)
This paper offers a gender approach to the impact of male migrationfrom Morocco to Europe on women left behind. The pertinence of the topic stems from the fact that very few studies have been conducted on the subject. It is believed that such studies will help in the understanding of the the phenomenon of migration and help to find solutions for some of the problems it poses. More and more Moroccan women suffer as a result of the migration of their husbands, sons,fathers, etc. Their suffering is not only due to separation from the loved ones but also to the dire economic and social conditions that a heavily patriarchal context does not help to alleviate.